Tensile, flexural, and water absorption properties of nano-silica enhanced kenaf/flax/glass fiber-reinforced epoxy hybrid biocomposites for sustainable development - Huang, Yang; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani; Nayak, Suhas Yeshwant (Taylor and Francis, 2025)
Fiber-reinforced composites are widely used in various industries. Hybridization improves the mechanical strength and versatility of these materials. Specifically, combining plant fibers with synthetic fibers enhances performance of biocomposites and environmental sustainability. This study fabricated five fiber-reinforced epoxy biocomposites (KKKKK, GKKKG, GKFKG, GFKFG, and GKGKG) from kenaf (K), flax (F), and glass (G) fibers using hand lay-up and vacuum bagging techniques. The epoxy matrix was mixed with nano-silica. These biocomposites were evaluated for tensile and flexural properties, water absorption, physical behavior, and specific strength. The results showed that hybrid fiber composites had significantly higher mechanical properties than pure kenaf composites. The tensile and flexural strengths of GFKFG were 103.79% and 196.32% higher than KKKKK, respectively. Additionally, hybrid biocomposites had superior moisture absorption, with GKFKG absorbing 45.59% and 48.52% less moisture in distilled water and artificial seawater, respectively, compared to KKKKK. Hybrid biocomposites also exhibited higher specific strength and thinner thickness, making them suitable for lightweight and compact structures. In conclusion, hybridizing kenaf fibers with flax and glass fibers enhances performance of biocomposites, promoting their use in marine, aerospace, and automotive applications, contributing to sustainable development.